A New Sonographic Weight Estimation Formula for Small-for-Gestational-Age Fetuses - Faschingbauer, Florian; Dammer, Ulf; Raabe, Eva; Kehl, Sven; Schmid, Matthias; Schild, Ralf L.; Beckmann, Matthias; Mayr, Andreas (Journal of Ultrasound in Medicine, 2016)
The purpose of this study was to develop a new specific weight estimation formula for small-for-gestational-age (SGA) fetuses that differentiated between symmetric and asymmetric growth patterns.A statistical estimation technique known as component-wise gradient boosting was applied to a group of 898 SGA fetuses (symmetric, n = 750; asymmetric, n = 148). A new formula was derived from the data obtained and was then compared to other commonly used equations.The new formula derived is as follows: estimated fetal weight = e^[1.3734627 + 0.0057133 × biparietal diameter + 0.0011282 × head circumference + 0.0201147 × abdominal circumference + 0.0183081 × femur length - 0.0000177 × biparietal diameter(2) - 0.0000018 × head circumference(2) - 0.0000297 × abdominal circumference(2) -0.0001007 × femur length(2) + 0.0397563 × I(sex = male) + 0.0064505 × gestational age (days) + 0.0096528 × I(SGA = asymmetric)], where the function I denotes an indicator function, which is 1 if the expression is fulfilled (sex = male; SGA type = asymmetric) and otherwise 0. In the whole study group and the 2 subgroups, the new formula showed the lowest median absolute percentage error, mean percentage error, and random error and the best distribution of absolute percentage errors within prespecified error bounds.The new formula substantially improves weight estimation in SGA fetuses.
EVALuna2:5572